Comparative research on earnings management, corporate governance, and economic value - Vieira, Elisabete S.; Madaleno, Mara, 1981-; Azevedo, Graça Maria do Carmo (Advances in finance, accounting, and economics (AFAE) book series., 2021)
"This book discusses the accounting policies firms use in different opportunistic circumstances in order to manage earnings, and to understand the corporate governance practices in different countries, and its relationship to firms' performance, and other dimensions of companies"--